Relevance Theory in the Performance of Revelation 17–19. Issue 3 (December 2015) - Perry, Peter S.
Relevance theory (RT) describes human communication as a cognitive process that tends to maximize contextual effects while minimizing processing effort. From an RT perspective, translation is a communication event in which a speaker/writer selects some contextual effects of a prior communication event to replicate with an acceptable amount of processing effort by new hearers in a different language. Performance is translation in that it shares the goal of replication of contextual effects; but while translators may desire verisimilitude above other goals, performers may have differently prioritized communicative objectives. Performance of a text provides Bible translators an opportunity to explore the effectiveness of verbal and non-verbal cues to maximize contextual effects and minimize processing effort for a specific audience. The performance of Revelation 17–19 offers a unique window into the cognitive effects of ambiguity and delayed processing, emotion and tone, space and distance that guide word choice, syntax, and visual formatting of a written translation. The non-verbal cues of performance correlate to the visual cues of a text in maximizing desired contextual effects while minimizing processing effort.